Ice Morph: An Automated Morphological Analyzer and English-Language Lookup Tool for Old Icelandic. - Tangherlini, Timothy R.; Vijunas, Aurelijus; Urban, Kryztof; Broadwell, Peter M. (Scandinavian Studies)
The article focuses on the digitization of Old Icelandic orthographies and texts using morphological analyzer and inflection engine through the IceMorph system. The system operates using various components including an automatic morphosyntactic tagging, lemmatization and disambiguation of Old Icelandic texts, the use of a user-friendly Web-based interface, and the use of a test corpus. A discussion on Old Icelandic spelling, inflection engine and programming is offered.